Entre aplausos, vaias e terra: uma análise da construção do discurso polêmico em torno do uso de agrotóxicos no Brasil - Quirino, Mayara (2021)
The discussion around the use of agrochemicals have become intense after the approval of the Law Project 6299 from 2002 – PL6299-2002, named as the Agrochemical Law, by a Commission of the House of Representatives in the year of 2018. Another discussed question was the intention of changing the name “agrochemical” to “pesticide”, which drives us to reflect upon discursive memory and amemory. Considering this panorama, this paper has the objective of analyzing how the discursive construction happens around the polemic of the use of agrochemicals in Brazil, mainly in what concerns nomenclatures. The corpus of study is composed by news about the agrochemicals question, presenting arguments both favorable and against the topic. The research is based in the French Discourse Analysis from the ideas of Maingueneau. We also used the recent discussions of Ruth Amossy (2017) around the argumentative character of the polemic discourse and the contributions by Marie-Anne Paveau (2015) about the concept of discursive amemory. Throughout the analysis, using a diachronic path, we identified linguistics and argumentative choices that are articulated in the building and propagation of the polemic in question. A blend was made among qualitative analyses and data generated from the program of textual treatment called Logiciel AntConc. This software allowed us to organize all the material that we believed to be essential for the study. We concluded that, besides the fact that Brazil has built a strong negative image in relation to the agrochemical in its discourses through history, the media does not follow this line of thoughts. There are more materials that are favorable than against, and even the impartial people, when we deepen the analysis, reveal a more prone argument toward the pro-agrochemical discourse. Besides that, we observed that the terms related to agrochemicals are not synonyms, but actually arguments of ideological groups, and that the media did not give the due attention that the question of the nomenclature deserves in the analyzed piece.